Aplikasi Augmented Reality Berbasis Vuforia dan Unity Pada Pemasaran Mobil - Mega, Fransisca Kristina (Universitas Trilogi, 2018)
In the current era of globalization, world development is increasingly difficult. Companies are required to be more innovative and creative in the marketing strategy of goods or services. Marketing strategies using media that create statistics cannot provide real-time feedback. Marketing strategies using media will increasingly attract the attention of consumers and become more interactive for consumers. Application of Augmented Reality technology based on Unity and Vuforia on marketing strategies that provide the best solutions in the automotive industry business world, consumers can see cars that are supported in realtime, types of cars that are not available in showrooms and marketing is done at certain events. Augmented Reality technology converts 2D images into 3D, this of course gives satisfaction to customers to see the cars offered. The results of this study use a marketing strategy with the application of Augmented Reality technology based on Unity and Vuforia to make it easier for consumers to see c rs in realtime and also provide convenience for manufacturers in terms of marketing and provide improvements in supplying their products. Kata Kunci - Augmented Reality, Vuforia, Unity, Pemasaran.